An Analysis of Business Marketing Strategies Using the Analytical Hierarchy Process (AHP): A Case Study of Dapur Ibuk MSME - Hamsiah Hamsiah; Nurafni Jami Putri; Adek Irma Rosi (The Future of Education Journal, 2026)
This study aims to analyze the marketing strategy of the MSME "Dapur Ibuk" using the Analytical Hierarchy Process (AHP) method. A common challenge faced by MSMEs is the efficient management of resources for product marketing. The AHP method was selected for this study because it enables the evaluation of alternative options based on specific criteria. The criteria utilized in this study include branding, quality, and price, while the strategic options considered are product development, digital marketing, and partnerships. The analysis recommends prioritizing quality improvement through product development. The results indicate that quality holds a weight of 51.2%, followed by branding at 38.7% and price at 10.1%. Regarding strategic priorities, product development ranks highest at 46.6%, followed by digital marketing at 37.3% and partnerships at 16.0%.